TRF2 cooperates with CTCF for controlling the oncomiR-193b-3p in colorectal cancer. (1st May 2022) - Dinami, Roberto; Petti, Eleonora; Porru, Manuela; Rizzo, Angela; Ganci, Federica; Sacconi, Andrea; Ostano, Paola; Chiorino, Giovanna; Trusolino, Livio; Blandino, Giovanni; Ciliberto, Gennaro; Zizza, Pasquale; et al.
Abstract: The Telomeric Repeat binding Factor 2 (TRF2), a key protein involved in telomere integrity, is over-expressed in several human cancers and promotes tumor formation and progression. Recently, TRF2 has been also found outside telomeres where it can affect gene expression. Here we provide evidence that TRF2 is able to modulate the expression of microRNAs (miRNAs), small non-coding RNAs altered in human tumors. Among the miRNAs regulated by TRF2, we focused on miR-193b-3p, an oncomiRNA that positively correlates with TRF2 expression in human colorectal cancer patients from The Cancer Genome Atlas dataset. At the mechanistic level, the control of miR-193b-3p expression requires the cooperative activity between TRF2 and the chromatin organization factor CTCF. We found that CTCF physically interacts with TRF2, thus driving the proper positioning of TRF2 on a binding site located upstream the miR-193b-3p host-gene. The binding of TRF2 on the identified region is necessary for promoting the expression of miR-193b3p which, in turn, inhibits the translation of the onco-suppressive methyltransferase SUV39H1 and promotes tumor cell proliferation. The translational relevance of the oncogenic properties of miR-193b-3p was confirmed in patients, in whom the association between TRF2 and miR-193b-3p has a prognostic value. Highlights: TRF2 affects microRNAs expression in CRC cells. TRF2 cooperates with CTCF to promote miR-193b-3p expression. miR-193b-3p mediates the tumor-promoting activity of TRF2 by targeting SUV39H1.